2014
DOI: 10.1007/s11581-014-1307-9
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of activated carbon paper by modified Hummer’s method and application as vanadium redox battery

Abstract: In this report, the activated carbon papers were prepared by the modified Hummer's method. After the treatment by the modified Hummer's method, the specific surface areas of carbon papers enlarged and the surfaces became wettability. Further, the electrochemical behaviors for the activated carbon papers were measured. They exhibit higher electrochemical activities for VO 2+ /VO 2 + redox reaction than the unactivated counterparts upon application as vanadium redox battery, which is ascribed to the synergistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…These indicte that the V 3+ /V 2+ redox reaction is controlled by diffusion process, and should be a quasi-reversible one. [60][61][62] By the Randles-Sevcik equation for the quasi-reversible process, the line slope is in proportion to the diffusion properties of active species. 60,61 Figure 9c shows that sulfonation treatment for CNTs has a positive effect on mass transfer for vanadium ions on them.…”
Section: Resultsmentioning
confidence: 99%
“…These indicte that the V 3+ /V 2+ redox reaction is controlled by diffusion process, and should be a quasi-reversible one. [60][61][62] By the Randles-Sevcik equation for the quasi-reversible process, the line slope is in proportion to the diffusion properties of active species. 60,61 Figure 9c shows that sulfonation treatment for CNTs has a positive effect on mass transfer for vanadium ions on them.…”
Section: Resultsmentioning
confidence: 99%
“…An energy efficiency around 70% at j = 150 mA·cm −2 was stable for at least 200 cycles. Carbon paper has been activated by a modified Hummer's method [223] and increased surface area and improved wettability were noticed. Improved performance as the positive VRFB electrode was also attributed to created functional groups.…”
Section: Structural Modification Of Carbonmentioning
confidence: 99%
“…GO that originated from graphite powder was prepared by the modified Hummer's method. 32 Subsequently, characterization of GO displayed a 2D sheet-like structure (Figure 1a), implying that GO was successfully fabricated. In addition, Figure 1b showed that GdDN had excellent dispersion, and the corresponding size was about 50 nm.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…GO that originated from graphite powder was prepared by the modified Hummer’s method . Subsequently, characterization of GO displayed a 2D sheet-like structure (Figure a), implying that GO was successfully fabricated.…”
Section: Results and Discussionmentioning
confidence: 99%